Financial accounting in Australia - Edwards, Lew; Goggett, John (John Wiley & Sons Australia, 1996)
Financial accounting in Australia.
Age Group: Adult
[V.1] text -- [V.2] study guide.
Previous ed.: 2000.
Includes index.
Keywords: Accounting -- Australia; Accounting -- Australia -- Problems, Exercises, Etc